Answer:
Jeremiah is correct
Step-by-step explanati
because any number divided by 0 is 0 and can be represented on a number line.
<h2>Anser</h2>
53
Step-by-step explanation:
(6-6)+7×7+4
=0+7×7+4
=7×7+4
=49+4
=53
i dont speak English 3456
To answer, it is assumed that e here is the Euler number which is equal to 2.718. Substitute this value to the e of the second equation to get the value of b.
b = 0.5(2.718^2) = 3.6945
Then, we substitute this value to the first equation to get the value of a.
a = 4(3.6945^2) = 54.498
Thus, the answer is approximately equal to 54.5.